APPLYING BASIC ERGONOMIC PRINCIPLES IMPROVES THE QUALITY OF TEACHING-LEARNING ENVIRONMENT IN THE JUNIOR SECONDARY SCHOOL - Ardana, I G.N.; Manuaba, A.; Adiputra, N.; Sutajaya, M. (Udayana University, 2011)
This study was conducted at the relatively young public junior secondary school at the district of Abiansemal and Administrative Region of Badung (SMPN-3) now aspiring to obtain national accreditation. In this context, the need was felt for improving the teaching-learning environment particularly in the school’s classrooms which might be conducive to maximizing the educational input and student performance. We studied the impacts of applying basic ergonomic principles to the design of some physical facilities (including redesign of the tables and chairs) in the classroom aiming to remediate present perceived deficiencies. Our samples were selected by using the multistage simple random sampling technique; and a total of 81 subjects consisting of 43 male and 38 female, volunteer students were recruited. The statistical methods used include descriptive statistics, analysis of normality and comparability. Our findings implied that interior ergonomic design intervention has led to the following outcomes: enhancing the student performance by decreasing eye strain by 44.76%; musculoskeletal complaints by 50.98%; and boredom by 14.17%. The beneficial outcomes of our intervention appeared to be obvious.